Efficacy and safety of prolonged-release hyaluronic acid derivative vaginal application in the postpartum period: a prospective randomised clinical trial - Claudio Gustavino; Paolo Sala; Nadia Cusini; Brunella Gravina; Cecilia Ronzini; Diletta Marcolin; Valerio Gaetano Vellone; Michele Paudice; Rossella Nappi; Sergio Costantini; Simone Ferrero; Fabio Barra (Annals of Medicine)
Introduction In puerperium, the hypoestrogenic state induced by delivery and subsequently sustained by lactation may lead to vaginal dryness, burning, and itching sensation, contributing to the onset of sexual dysfunction.Material and methods This was a prospective, randomized, controlled, open-label study (NCT04560283) for evaluating the effects of application of a prolonged-release hyaluronic acid derivative vaginal gel in restoring sexual function during the postpartum period. Eighty-five patients were randomized to apply prolonged-release Hydeal-D 0.2% vaginal gel (Fidia Farmaceutici, Abano Terme, Italy; n = 43) every three days for 12 consecutive weeks or expectant management (n = 42).Results Women undergoing treatment had a more elevate increase in Female Sexual Function Index (FSFI) total score (+15.1 ± 11.9 vs +6.5 ± 8.9, p < 0.001) and a higher decrease in vaginal pH (−1.2 ± 0.7 vs −0.2 ± 1.1; p < 0.001). Moreover, the proportion of vaginal smears with maturation index (VMI) >65 was significantly higher in patients treated (80.6% vs 35.3%; p = 0.004). Edinburgh Postnatal Depression Scale (EPDS) decreased significantly in both groups with no inter-group difference (p = 0.459). Only two cases (4.8%) of moderate vaginal burning sensation were reported in patients undergoing local vaginal therapy.Conclusions The results of our study demonstrated that hyaluronic acid derivative vaginal gel (Hydeal-D) was able to improve sexual function of puerperal women in the short-term treatment.KEY MESSAGEIn the puerperium, the hypoestrogenic state induced by delivery and subsequently sustained by lactation may lead to vaginal dryness, burning, and itching sensation, contributing to the onset of sexual dysfunction.Hydeal-D is a prolonged-release hyaluronic acid derivative characterised by elevated resistance to enzymatic breakdown. During puerperium, its local application may improve the vaginal microenvironment by ensuring a better migration and proliferation of cells involved in local tissue repair.Among puerperal women, Hydeal-D vaginal gel causes a significant improvement of sexual function, including desire, arousal, and lubrification, compared to expectant management. Furthermore, it leads to a decrease in vaginal pH and an increase of the trophic status of vaginal epithelium.